Teaching Puzzle-Solving Skills to Students with Multiple Disabilities via a Tablet Computer - Cetin, Muzeyyen Eldeniz; Cay, Evgin (Egitim ve Bilim, 2021)
The aim of this study was to teach the puzzle-solving skills to students with multiple disabilities by using a tablet computer and enable them to demonstrate this skill fluently afterwards. The research was conducted in two phases. In the first phase, the effectiveness of direct instruction in teaching puzzle-solving skills to students with multiple disabilities by using a tablet computer was investigated. Also, generalization effect of the acquired skills on various materials and their maintenance effect after 1, 3 and 4 weeks were evaluated. In this phase of the study, multiple probe design with probe trials across subjects, one of the single-subject research designs, was used. In the second phase, it was aimed to increase the fluency of those students in puzzle-solving on a tablet computer. Similar to the first phase, a single-subject design, the changing criterion model was used in the second phase. Three participants, two male and one female, were involved in the study. All sessions were held as one-to-one instruction arrangements. The study revealed that direct instruction was effective in teaching puzzle-solving skills, the participants demonstrated the target skills at the end of weeks 1, 3 and 4. In addition, it was observed that they could generalize those skills to different materials, settings and people, and they improved their fluency. Araştırmanın amacı, çoklu yetersizliği olan öğrencilere tablet bilgisayar aracılığı ile yapboz yapma becerisinin kazandırılması ve kazanılan beceriyi akıcı bir şekilde sergilemelerini sağlamaktır. Araştırma iki aşamada gerçekleştirilmiştir. Birinci aşamada, çoklu yetersizliği olan öğrencilere tablet bilgisayar aracılığı ile yapboz yapma becerisinin kazandırılmasında, öğrenilen becerinin farklı materyallere, ortamlara ve kişilere genellenmesinde ve uygulama bittikten 1,3 ve 4 hafta sonra sürdürülmesinde doğrudan öğretim yönteminin etkisi incelenmiştir. Araştırmanın birinci aşamasında; tek denekli araştırma yöntemlerinden denekler arası yoklama denemeli çoklu yoklama modeli kullanılmıştır. Araştırmanın ikinci aşamasında ise; çoklu yetersizliği olan öğrencilerin kazandıkları tablet bilgisayar aracılığı ile yapboz yapma becerilerinin akıcılığını artırmak hedeflenmiştir. Bu aşamada da tek denekli araştırma modellerinden değişen ölçütler modeli kullanılmıştır. Araştırmaya, ikisi erkek, biri kız olmak üzere toplam üç denek katılmıştır. Araştırmada tüm oturumlar bire bir öğretim düzenlemesi biçiminde yapılmıştır. Araştırma sonucunda yapboz yapma becerisinin öğretiminde doğrudan öğretiminin etkili olduğu, öğrencilerin öğretim sona erdikten 1,3 ve 4 hafta sonunda öğrenilen beceriyi korudukları ve farklı materyallere, ortamlara ve kişilere genelledikleri ve yapboz yapma becerisinde süre açısından akıcılık kazandıkları tespit edilmiştir.